Z zagadnień słownictwa ogólnotunezyjskiego - Oueslati, Jamila (Investigationes Linguisticae, 2008)
This article is devoted to some problems of the Tunisian lexicon from the point of view of contact between the Tunisian Arabic language community and other language communities. The terms Tunisian Arabic language community, General Tunisian Arabic and Pan-Arabic language community are first defined. Contacts between the Tunisian Arabic language community and other language communities are discussed while part of the lexicon stemming from Arabic and French is analyzed.